2019
DOI: 10.1111/apm.12925
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to a specific peptide epitope of human Hsp60 (ATVLA) with homology to Helicobacter pylori HspB in H. pylori‐infected patients

Abstract: Chmiela M. Autoantibodies to a specific peptide epitope of human Hsp60 (ATVLA) with homology to Helicobacter pylori HspB in H. pylori-infected patients. APMIS 2019; 127: 139-149.Helicobacter pylori (Hp) may initiate autoimmunity as a result of molecular mimicry. The aim of this study was to compare the level of IgG antibodies to a specific epitope (P1 peptide) of human heat shock protein (Hsp)60 homologous to Hp Hsp60 (HspB) in the sera of healthy donors (HD), patients with Hp-related gastritis or coronary hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…Molecular mimicry and the consequent potential cross-reactivity following infections have been repeatedly described in humans. [1][2][3][4][5][6][7][8][9][10][11][12] Such cross-reactivity is not evident in experimental infections of primates. 13 Actually, following preclinical studies performed in primates [14][15][16][17][18] as recommended by the Food and Drug Administration, 19 the reports declare that primate active immunization by pathogen vaccine administration is well tolerated and exempt of relevant events.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular mimicry and the consequent potential cross-reactivity following infections have been repeatedly described in humans. [1][2][3][4][5][6][7][8][9][10][11][12] Such cross-reactivity is not evident in experimental infections of primates. 13 Actually, following preclinical studies performed in primates [14][15][16][17][18] as recommended by the Food and Drug Administration, 19 the reports declare that primate active immunization by pathogen vaccine administration is well tolerated and exempt of relevant events.…”
Section: Introductionmentioning
confidence: 99%
“…In Western but not Asian H pylori strains, a linear glucan-heptan linker between these two parts of LPS was identified. This dependence was also shown by the stimulation by ATVLA of human THP-1Blue™ monocytes for the secretion of proinflammatory cytokines 31. IgG class antibodies to synthetic P1 peptide containing ATVLA were detected in patients with gastritis or coronary heart disease (CHD) infected with H pylori as well as in Cavia porcellus inoculated with H pylori, but not in uninfected individuals or asymptomatic H pylori carriers, suggesting a potential role of such antibodies, possibly autoreactive, in the development of H pylori-related disease.…”
mentioning
confidence: 60%
“…The study carried out by Gonciarz et al, 31 Furthermore, it was shown that the H pylori genetic region, known as integrating conjugative elements of H pylori T4SS, contains a novel type of T4SS, which is considered as a H pylori virulence factor. 33 However, the structure containing genes encoding components of this system, and the interactions between this T4SS and other virulence factors remain unknown.…”
Section: New Aspects Of Other Virulence Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…tuberculosis, different herpes virus infections, Dengue virus infections [9,10], hepatitis, or events summarized as "common cold" and "feverish infection" (for review see [5]). This suggests the action of viral or bacterial proteins mimicking antibody targets as first initiating events, as seen in patients with Guillain Barré Syndrome [11,12] or some other antibody-driven diseases [13,14].…”
Section: Introductionmentioning
confidence: 99%